2022
DOI: 10.1038/s41467-022-34605-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a third BNT162b2 mRNA COVID-19 vaccination during pregnancy: a national observational study in Israel

Abstract: The Centers for Disease Control (CDC) recommend a third dose of COVID-19 vaccine for pregnant women, although data regarding effectiveness during pregnancy are lacking. This national, population-based, historical cohort study of pregnant women in Israel, delivering between August 1, 2021 and March 22, 2022, aims to analyze and compare the third and second doses’ vaccine effectiveness in preventing COVID-19-related hospitalizations during pregnancy during two COVID-19 waves (Delta variant in the summer of 2021 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Finally, during the Omicron period, receiving a third vaccine dose resulted in significantly improved vaccine effectiveness against hospitalization compared with two doses only. 25 (Fig. 3).…”
Section: What Is the Benefit Of A Booster Dose In Pregnancy?mentioning
confidence: 97%
“…Finally, during the Omicron period, receiving a third vaccine dose resulted in significantly improved vaccine effectiveness against hospitalization compared with two doses only. 25 (Fig. 3).…”
Section: What Is the Benefit Of A Booster Dose In Pregnancy?mentioning
confidence: 97%
“… 2 , 3 Although pregnant women were excluded from COVID-19 vaccine clinical trials, limiting initial data on effectiveness in pregnancy, 4 other studies have shown that mRNA COVID-19 vaccines are effective in pregnant women. 2 , 3 Three studies of pregnant women, published in 2022, have assessed disease severity 5 and vaccine effectiveness 2 , 6 during the period of omicron variant predominance. Using population-level data among women from Scotland with SARS-CoV-2 infection during pregnancy, authors found that, compared with the period of delta variant predominance, the omicron period was associated with significantly lower risk of preterm birth and severe illness during pregnancy.…”
mentioning
confidence: 99%
“… 5 In studies from the USA and Israel, monovalent mRNA COVID-19 vaccination was less effective during the omicron period than the delta period and effectiveness waned over time, particularly during the omicron period in pregnant women who had not received a COVID-19 booster vaccination. 2 , 6 …”
mentioning
confidence: 99%
“…Vaccine-induced antibody titers may be similar to those produced in non-pregnant women, with antibody production starting two weeks from the first dose [ 166 ]. Benefits of the vaccine for the mother include reduced risk of infection, lower maternal hospitalization, and need for intensive care admission [ 167 , 168 ]. Vaccination in pregnant women also benefits the neonate due to the passive transfer of antibodies.…”
Section: Strategies For Preventing Perinatal Covid-19mentioning
confidence: 99%